Effectiveness of water permeable joint filling materials for weed prevention in paved areas. (16th May 2014) - De Cauwer, B; Fagot, M; Beeldens, A; Boonen, E; Bulcke, R; Reheul, D; Kempenaar, Corné
Summary The recent phase‐out of herbicide use on public pavements in Flanders has triggered the development of alternative strategies for weed prevention and control. In this study, growth chamber experiments investigated the ability of various water permeable joint filling materials for pavements to prevent weed growth. Joint fillers included in the tests comprised five innovative (iron slag sand, polymeric bound sand and three sodium silicate enriched fillers) and eight standard joint fillers (four fine materials, for example, sea sand, white sand, sandstone and fine limestone, and four coarse materials based on porphyry and limestone). Their ability to suppress weeds was investigated by examining seedling emergence and biomass production of seven test species in pure or organically polluted (5%, 10%, 20%, 40% and 80% compost by volume) filler substrate. Selected test species were dominant, hard‐to‐control weeds found on pavements. Seedling emergence and weed biomass were lowest in iron slag sand, polymeric bound sand and most sodium silicate enriched fillers, irrespective of pollution level or test species. Within standard joint fillers, pure white sand, sandstone and the coarse materials also reduced biomass, but their inhibitory effect dropped quickly once organically polluted, in contrast to fine limestone and sea sand for which weed suppression lasted longer (up to 40% compost by volume). Weed suppression of joint fillers was species specific. Our results show that there is potential for preventing weed growth using fillers that prevent the growth of a wide spectrum of plant species over a long period.